Effects of cinnamon and rosemary oils on egg production, egg quality, hatchability traits and blood serum mineral contents in laying quails (Coturnix coturnix Japonica) - Simsek, Ulku Gulcihan; Ciftci, Mehmet; Ozcelik, Mehtap; Azman, Mehmet Ali; Tonbak, Fadime; Ozhan, Nejla (Ankara Univ Press, 2015)
This study was carried out to evaluate the effects of cinnamon (CO), rosemary (RO) and a mixture (MO) of these plants oil on egg production, feed intake, feed conversion rate, external and internal egg quality, blood serum mineral contents and hatchability traits in different sex ratios of [1/3 and 1/5, (male/female)] in laying quails. A total of 192 quail were distributed into special cages (12 quails/per cage) including three experimental diets and control. The experiment was continued two months. At the end of the study, 12 birds from each group were slaughtered in order to collect blood samples. The levels of Cu, Co, Cr, Zn, Fe, K, Na and Mg in serum were determined. The highest egg weight was found in RO group, while it was lowest in MO group (P<0.05). Addition of diatery CO improved hen-day egg production as well as feed conversion rate (P<0.05). Feed intake was found to be similar among the groups (P>0.05). While egg shell rate increased in CO group (P<0.05), the ratios of egg yolk, egg albumen and shape index did not differ among the treatments (P>0.05). Although the effect of diets implemented in the experimental groups on the fertility was found to be significant (P<0.05) this effect on the hatchability traits in both sex ratios was not significant (P>0.05). While the serum K level was significantly higher in CO group (P<0.05) the level of Zn in group CO (P=0.078) and the level of Co in group RO were found slightly higher (P=0.086). The other findings of mineral contents were similar among the groups (P>0.05). Consequence of this study showed that CO had a positive effects on egg production and egg shell quality. Mixture of CO and RO had negative effects on egg weight and cumulative egg weight.
Tarçın ve biberiye yağlarının yumurtacı bıldırcınlarda (Coturnix coturnix Japonica) yumurta üretimi, kabuk kalitesi, kuluçka özellikleri ve serum mineral düzeyleri üzerine etkileri
Keywords: Cinnamon and rosemary oils; hatchability; performance; quail; serum mineral